2012
DOI: 10.1021/ct300519v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Provide Atomistic Insight into Hydrogen Exchange Mass Spectrometry Experiments

Abstract: It is now clear that proteins are flexible entities that in solution switch between conformations to achieve their function. Hydrogen/Deuterium Exchange Mass Spectrometry (HX/MS) is an invaluable tool to understand dynamic changes in proteins modulated by cofactor binding, post-transductional modifications, or protein-protein interactions. ERK2MAPK, a protein involved in highly conserved signal transduction pathways of paramount importance for normal cellular function, has been extensively studied by HX/MS. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…The longest atomistic MD trajectory previously used for HX analysis was three orders of magnitude shorter (90 ns) (36). Rather than attempting to identify the O state, that study correlated the trajectory-averaged (essentially C-state) amide solvent access with the number of exchanged hydrogens (detected by mass spectrometry) for a set of peptide fragments (36). However, the strong linear correlation thus obtained seems to be spurious, largely resulting from the trivial increase of both variables with peptide size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longest atomistic MD trajectory previously used for HX analysis was three orders of magnitude shorter (90 ns) (36). Rather than attempting to identify the O state, that study correlated the trajectory-averaged (essentially C-state) amide solvent access with the number of exchanged hydrogens (detected by mass spectrometry) for a set of peptide fragments (36). However, the strong linear correlation thus obtained seems to be spurious, largely resulting from the trivial increase of both variables with peptide size.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physical significance of the PF is obscured by our ignorance about the structure and dynamics of the O state. Several attempts have been made to correlate experimental PFs with physical attributes of the amides, such as solvent contact (33)(34)(35)(36)(37), burial depth (38), intramolecular H-bonds (35,(38)(39)(40), packing density (38,41), or electric field (42). Where significant correlations have been found, they suggest that the chosen attribute can serve as a proxy for the propensity for C → O fluctuations.…”
Section: Significancementioning
confidence: 99%
“…Recently, Petruk et al 17 used MD simulations and a metric based on average SASA of NH and the number of H-bonds with water molecule as the basis for the binary decision if exchange would occur or not in the ERK2 MAP kinase system. The authors were successful in explaining some of the observed differences between apo and holo dynamics in terms of their metrics.…”
Section: Introductionmentioning
confidence: 99%
“…The most pronounced decrease in backbone H/D exchange was observed for peptides 3 (16-26) and 4 (23-28), both containing Arg24, and peptides 7 (37-47) and 8 (40)(41)(42)(43)(44)(45)(46)(47), both containing Arg43 from a neighboring monomer subunit (Figure 2a, c). Other regions located close to the active site [peptides 10 (50-72), 13 (95-103), and 19 (178-182)], and peptides 1 (2-10) and 10 (50-72) from adjacent subunit are under the influence of the P i .…”
Section: Phosphate Binding Is Affected By Arg24ala Mutation and Activmentioning
confidence: 97%
“…Different calculation strategies are employed to link protein dynamics with amide H/DX reaction rates by analyzing ensemble representation of the protein structure [35][36][37][38][39]. All-atom molecular dynamics (MD) simulations can be used to probe protein structure flexibility caused by frequent atomic movements [40,41] but other fluctuations relevant for H/DX occur on a time scale longer than it is currently possible to simulate with average computation resources. Recently, McAllister and Konermann carried out detailed structureexchange rate relationship analysis by combining MD simulations and H/DX data and showed that significant fraction of amide hydrogens exist with H/DX protection different than can be predicted by any of the current models proposed to explain particular H/DX pathway [42].…”
mentioning
confidence: 99%